La evolución de las misiones civiles de la política europea de seguridad y defensa - Ruiz Campillo, Xira (UNISCI Discussion Papers, 2008)
The European Union has deployed thirteen civilian missions since 2003 through its European Security and Defence Policy. The analysis of the missions in Bosnia and Herzegovina, in Macedonia, in Aceh, Democratic Republic of the Congo, Iraq and Kosovo, among others, proves the Union’s interest in the international security area. The paper goes through different ESDP civilian missions analysing their aims and their complexity